The impact of mouth breathing on craniofacial development: Dampak mouth breathing terhadap perkembangan kraniofasial - Fadilah Abdullah; Nasyrah Hidayati (Makassar Dental Journal PDGI Makassar, 2026)
Mouth breathing is a harmful habit that deviates from the normal practice of breathing through the nose, and its aetiology is multifactorial. Various causes of mouth breathing include genetic factors, bad habits, and nasal obstruction due to tonsillar hypertrophy, nasal polyps, a deviated nasal septum, or sinusitis. The impact of mouth breathing on oral and craniofacial development remains a subject of debate, although children who habitually breathe through their mouths often exhibit certain characteristics, known as the ‘adenoid face’, including an incompetent upper lip, retroposition of the hyoid bone, a ‘V’-shaped up-per jaw arch, and Class II malocclusion. Changes in facial growth in individuals who breathe through their mouths have been studied by various healthcare professionals, including doctors and orthodontists, although much remains to be learnt about the relationship between mouth breathing and oral and cranio-facial development. This article discusses the impact of mouth breathing on craniofacial development. It is concluded that mouth breathing can influence cra-niofacial development through changes in the upper and lower jaw arches, profile, and muscles.